Informational Supervision Approach as an Effort to Improve the Quality of Learning in Schools - Zakiya, Nabila; Simatupang, Umy Nadrah; Aulia, Yenni; Marsidin, Sufyarma; Rifma, Rifma (Postgraduate School, Universitas Negeri Padang, 2023)
collaboration in order to educate the nation's children. The elements contained in it are also inseparable from the components which are considered as something very important in supporting effectiveness and quality. The role of the principal is very close to quality improvement by taking responsibility as a supervisor. Sri Banum Muslim (2013: 38) summarizes supervision